2020
DOI: 10.1038/s41598-020-70059-1
|View full text |Cite
|
Sign up to set email alerts
|

Inaccurate offset restoration in total hip arthroplasty results in reduced range of motion

Abstract: Offset restoration in total hip arthroplasty (THA) is associated with postoperative range of motion (ROM) and gait kinematics. We aimed to research into the impact of high offset (HO) and standard stems on postoperative ROM. 121 patients received cementless THA through a minimally-invasive anterolateral approach. A 360° hip ROM analysis software calculated impingement-free hip movement based on postoperative 3D-CTs compared to ROM values necessary for activities of daily living (ADL). The same model was then r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
2
15
0
2
Order By: Relevance
“…Inaccurate center of rotation (COR) restoration is associated with impingement, reduced hip abductor strength, altered gait kinematics, reduced postoperative hip range of motion, trochanteric pain, instability, and higher rates of wear [19,[27][28][29]. The horizontal distance of the COR is also considered as the acetabular offset.…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate center of rotation (COR) restoration is associated with impingement, reduced hip abductor strength, altered gait kinematics, reduced postoperative hip range of motion, trochanteric pain, instability, and higher rates of wear [19,[27][28][29]. The horizontal distance of the COR is also considered as the acetabular offset.…”
Section: Discussionmentioning
confidence: 99%
“…This has important clinical implications. Using this type of stem could prevent the risk of dislocation in high-risk patients [ 35 ], and these stems are an essential option for restoring biomechanics and enabling a free range of motion without impinging on the activities of daily living in a substantial proportion of patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prosthetic ROM in those directions was measured using a previously reported method [ 9 ]. Several reports have shown that the ROM was affected by the femoral offset and head diameter [ 10 13 ]; therefore, in all cases, the femoral offset was standardized to a stem with a standard offset type and the minimum neck length for each stem. The femoral head diameter was standardized to 32 mm, and the prosthetic ROM was measured.…”
Section: Methodsmentioning
confidence: 99%